Seroprevalence of Bactericidal, Specific IgG Antibodies and Incidence of Meningitis Due to Group A Neisseria meningitidis by Age in Burkina Faso 2008 - Trotter, Caroline L.; Yaro, Seydou; Njanpop-Lafourcade, Berthe-Marie; Drabo, Aly; Kroman, Sita S.; Idohou, Regina S.; Sanou, Oumarou; Bowen, Leah; Findlow, Helen; Diagbouga, Serge; Gessner, Bradford D.; Borrow, Ray; et al. (PloS one, 2013)
We investigated serological correlates of protection against Neisseria meningitidis serogroup A (NmA) in Burkina Faso before the introduction of NmA conjugate vaccine. We collected blood from a representative sample (N = 1022) of Bobo-Dioulasso residents. Sera were evaluated for serum bactericidal antibody (SBA) activity against NmA strains of immunotype L11 (F8238) and L10 (3125) and NmA-specific IgG. Seroprevalence was compared to the age-specific NmA meningitis incidence in Bobo-Dioulasso during March 2007-February 2008. Meningococcal carriage was evaluated in a subset (N = 538). Geometric mean titres (GMT)/concentrations (GMC) of SBA and NmA-specific IgG increased with age, peaking around age 20 years. Overall, 70% of our sample had NmA-specific IgG ≥2 ug/mL. Meningitis incidence was highest in those aged <6 months and 5-19 years. No NmA carriers were found. Compared to the reference strain SBA, GMTs were higher against a locally isolated strain and around 40-fold lower against Dutch strain 3125. This study provides estimates of natural immunity to NmA, according to a variety of antibody measures, which will be helpful in ascertaining antibody persistence after MenAfriVac™ introduction. Age-specific seroprevalence of reference strain SBA titres most likely reflects exposure to meningococci and consecutive reactive immunity. We could not define any serological correlate of protection.